BIOSTRATIGRAPHY AND PALEOENVIRONMENTAL ANALYSIS OF THE LOWER MIOCENE QOM FORMATION (JAAM AREA, CENTRAL IRANIAN BASIN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Lower Miocene sediments from a previously not investigated outcrop of the Qom Formation (Central Iranian Basin) were studied for their foraminiferal and calcareous nannofossil content. The studied stratigraphic record is assigned to the upper part of calcareous nannofossil NN2 Zone/CN1c Subzone and to the benthic foraminiferal Borelis melo melo Zone of Burdigalian age. The diversity indices, benthic foraminiferal morphogroups, and quantitative analyses of assemblages (principal component and cluster analysis) suggest an overall shallow-marine depositional environment. This interpretation is well constrained based on the dominance of the B1 benthic foraminifera morphotype with biconvex, trochospiral calcareous test, and epifaunal habitat. The identified six cluster groups of benthic foraminiferal assemblages are confirmed by the principal component analysis too, and their distribution along the studied section argue for dynamic changes of the environment. This is well exemplified by a more or less constant shallowing, then deepening trend of the environment as revealed by the shifting from the high diversity, shallow-shelf assemblages of Cluster 5 and 6 toward the low diversity, near-shore Ammonia tepida and Porosononion subgranosus assemblage (Cluster 1), and back.
Keywords: Benthic foraminifera; calcareous nannofossils; Burdigalian; paleoecology; paleogeography